?The Wheel of My Work?: Community Health Worker Perspectives and Experiences with Facilitating Refugee Access to Primary Care Services (Mary Ann Liebert, 2021)
Purpose: Community health workers (CHWs) are trusted community leaders and public health workers dedicated to promoting the health and well-being of community members. CHWs, who share similar language and culture, work with refugee communities that are often missed in traditional U.S. health systems. CHWs help refugees gain access to health care through culturally appropriate strategies. However, the scope of their study as cultural brokers with regard to refugee health access is largely unknown in the peer-reviewed literature. This qualitative research study used a constructivist grounded approach to examine the extent to which CHWs helped refugee clients gain access to the health care system. Methods: Data were collected through interviews with a purposeful sample of 10 CHW participants affiliated with a primary care access program in Greensboro, North Carolina. Results: The diagram derived from this study provided a schema that allowed for an improved understanding of CHW perspectives and experiences when connecting refugee clients to the health care system. Conclusions: Further research incorporating CHW voices is recommended because CHWs are instrumental in improving the health and well-being of refugees.